Behavioral Variation in the Pygmy Halfbeak Dermogenys collettei: Comparing Shoals With Contrasting Ecologies - Devigili, Alessandro; Fernlund Isaksson, Erika; Puniamoorthy, Nalini; Fitzpatrick, John L. (Frontiers in Ecology and Evolution, 2021)
Variation in biotic and abiotic factors among populations affects individual behaviors by transforming the social landscape and shaping mating systems. Consequently, describing behaviors in natural populations requires consideration of the biological and physical factors that different individuals face. Here, we examined variation in socio-sexual and locomotor behaviors in a small, livebearing, freshwater fish, the pygmy halfbeak Dermogenys collettei, across natural populations in Singapore. The pygmy halfbeak is a surface feeding fish that spends most of the time near the water surface, making it ideal for non-invasive behavioral observations. We compared behaviors between sexes among 26 shoals while simultaneously accounting for environmental variation. We demonstrated that sexual interactions and locomotor behaviors differed among shoals with varying levels of canopy cover and water flow. Specifically, in areas with greater canopy cover, sexual interactions decreased, whereas time spent in a stationary position increased. Sexual interactions were more numerous in still water, where fish spent less time swimming. Variation in the expression of socio-sexual and locomotor behaviors were not associated with differences in the amount of aquatic vegetation, water depth or halfbeak shoal size. Agonistic interactions were robust to environmental effects, showing little variation among environments. However, there were strong sex effects, with males performing more agonistic behaviors and spending less time in a stationary position compared to females, regardless of the environment. Moreover, sexual interactions, measured as actively performed by males and passively received by females, were on average more frequent in males than in females. Our findings help us explore the proximal causes of intraspecific behavioral variation and suggest that fundamental information on socio-sexual behaviors from wild populations can lead to a better understanding of how sexual selection operates when the strength of natural selection varies across environments.